1984
DOI: 10.1002/star.19840361005
|View full text |Cite
|
Sign up to set email alerts
|

Production and Measurement of Starch Damage in Flour. Part 2. Damage Produced by Unconventional Methods

Abstract: The relationship between two parameters of starch damage namely enzyme susceptibility and amylose extractability was examined in starch and in hard and soft flours ground by three unconventional methods. Variations in the relationship were as great in the starch series as in the flours, demonstrating that the effects of particle properties on the efficiency of one or other method of determination were not responsible. It is suggested that the two parameters are capable of independent variation since, in a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…One of the major impacts of SM grinding on FRF composition was higher starch damage compared to FRF from either DD or SS grinding (Tables V and VI). This effect was predictable from wheat milling research that has shown that smooth roll grinding during reduction imparts greater starch damage than fluted roll grinding (Evers et al 1984), and that power consumption during grinding is Fig. 4.…”
Section: Physicochemical Characteristics Of Fiber-rich Fractionmentioning
confidence: 73%
“…One of the major impacts of SM grinding on FRF composition was higher starch damage compared to FRF from either DD or SS grinding (Tables V and VI). This effect was predictable from wheat milling research that has shown that smooth roll grinding during reduction imparts greater starch damage than fluted roll grinding (Evers et al 1984), and that power consumption during grinding is Fig. 4.…”
Section: Physicochemical Characteristics Of Fiber-rich Fractionmentioning
confidence: 73%
“…Accompanying the increased granule swelling is an increase in starch polymer molecule solubility and an increase in susceptibility of the damaged starch granules to the action of amylases. In fact, early methods for determination of the relative amounts of damaged starch in samples were based on measurements of solubilized AM or susceptibility to hydrolysis by α-amylase (Alsberg & Griffing 1925, Pulkki 1938, Jones 1940, Sandstedt & Mattern 1960, Williams & LeSeeleur 1970, Dodds 1971, Evers et al 1984a), but Evers et al (1984b) determined that the two parameters were independent of each other. Tamaki et al (1997aTamaki et al ( , 1998 also found increases in susceptibility of damaged starch granules to the action of amylases.…”
Section: Effects On Starch Characteristicsmentioning
confidence: 99%
“…Starch is the main component in most cereal grains, normally accounted for more than 50% of grain weight, and thus the changes in starch structures, e.g., those caused by milling, can largely affect the functional properties of flour, such as pasting properties, swelling properties, solubility, and digestibility . For examples, mild damage to starch granules in flour as the result of grain milling increases loaf‐volume of bread and produces noodles with good texture; however, severe damage to starch granules can lead to diminishing qualities of bread and noodles .…”
Section: Introductionmentioning
confidence: 99%